2008
DOI: 10.1007/s00705-008-0234-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of various types and P25 subtypes of Beet necrotic yellow vein virus in Germany and other European countries

Abstract: The distribution of various Beet necrotic yellow vein virus (BNYVV) genotypes was studied using beet samples received from Germany and neighbouring countries. Almost exclusively B type BNYVV was detected in Germany, whereas in neighbouring countries BNYVV A types with different compositions of the amino acid tetrad in positions 67-70 of the RNA-3-encoded P25 are widely distributed. Neither A types nor the P type have been able to become established in Germany in the past decades, although there must have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 23 publications
1
26
0
3
Order By: Relevance
“…The third strain group, designated as pathotype P, contains an additional genomic RNA (RNA 5) and was found at first in the region around Pithiviers, France (Koenig et al 1997), later in Kazakhstan (Koenig and Lennefors 2000) and more recently in the UK (Ward et al 2007). Other RNA 5-containing isolates have been reported in Japan, China Kiguchi et al 1996;Miyanishi et al 1999), the UK (Harju et al 2002;Ward et al 2007) and Germany, where one field has been found to be infested by an RNA 5-containing East Asian isolate (Koenig et al 2008). On the basis of sequence variability, isolates containing a fifth RNA molecule have been classified into P-and J-types for the European and Asian isolates respectively .…”
Section: Introductionmentioning
confidence: 95%
“…The third strain group, designated as pathotype P, contains an additional genomic RNA (RNA 5) and was found at first in the region around Pithiviers, France (Koenig et al 1997), later in Kazakhstan (Koenig and Lennefors 2000) and more recently in the UK (Ward et al 2007). Other RNA 5-containing isolates have been reported in Japan, China Kiguchi et al 1996;Miyanishi et al 1999), the UK (Harju et al 2002;Ward et al 2007) and Germany, where one field has been found to be infested by an RNA 5-containing East Asian isolate (Koenig et al 2008). On the basis of sequence variability, isolates containing a fifth RNA molecule have been classified into P-and J-types for the European and Asian isolates respectively .…”
Section: Introductionmentioning
confidence: 95%
“…J type isolates possess two deletions at amino acid positions 77 and 227-229 in p26, compared to the P type (Schirmer et al, 2005). P type BNYVV only occurs in France, the United Kingdom and Kazakhstan (Koenig et al, 1997;Koenig and Lennefors, 2000;Ward et al, 2007), and the J type mainly occurs in Japan, China and a single field in Germany (Chiba et al, 2011;Li et al, 2008;Koenig et al, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…A and B types contain four RNAs, and the differences at amino acid positions 62, 103 and 172 of the CP gene allowed us to distinguish between A type (T 62 S 103 L 172 ) and B type (S 62 N 103 F 172 ) isolates (Miyanishi et al, 1999). The A type BNYVV has a worldwide distribution (Schirmer et al, 2005), whereas the B type seems to be limited to few areas in Europe (Koenig et al, 2008), Japan (Miyanishi et al, 1999) and China (Li et al, 2008). P and J types possess the fifth RNA (RNA5) and share about 96% sequence identity (Ward et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…the A, B and P types, have highly conserved genomes. Nucleotides 199-210 of the P25-coding region, however, show considerable sequence variation, especially in A type BNYVV (Tamada et al, 2003;Meunier et al, 2003;Schirmer et al, 2005;Ward et al, 2007;Kutluk Yilmaz et al, 2007;Li et al, 2008;Koenig et al, 2008). This stretch of nucleotides codes for the P25 aa 67-70, which in the following will be referred to as the 'tetrad'.…”
mentioning
confidence: 99%